Cultural Value Shifting in Pronoun Use. (February 2016) - Yu, Feng; Peng, Theodore; Peng, Kaiping; Tang, Shi; Chen, Chuan Shi; Qian, Xiaojun; Sun, Pei; Han, Tingting; Chai, Fangyuan
By investigating the use of first-person pronouns in nine languages using the Google Ngram Database, we examined the degree to which different cultural values skewed toward individualism or collectivism over a span of 59 years. We found that in eight of nine languages (British English being the exception), first-person singular pronouns (vs. first-person plural pronouns) have become increasingly prevalent, which in turn points to a rising sense of individualism. British English showed a U-shaped curve trend in the use of first-person singular pronouns (vs. first-person plural pronouns). Although they initially decreased, British English's first-person singular pronouns (vs. first-person plural pronouns) use was higher than most other languages throughout the whole period. Chinese displayed a fluctuating pattern wherein the use of first-person singular pronouns (vs. first-person plural pronouns) increased in recent periods. The dynamics of cultural change and culture diversity were discussed.